The Christianization of political discourse: reflections on the Irish evidence - O'Brien, C (Johns Hopkins University Press, 2022)
A wealth of political writings survives from early Christian Ireland. While traditionally this material has been understood in terms of a dichotomy between "pagan" and "Christian," recent scholarship has borrowed the category of the "secular" from late antique studies to make sense of early Irish intellectual culture and its political discourses. This article builds on this trend to reveal, through close examination of seventh-century Irish writings, a multitude of differently Christianized discourses existing simultaneously, sometimes even within a single text. Just as the boundary between the "pagan" and the "secular" was not fixed, so too the boundary between the "Christian" and the "secular," giving rise to many different ways late antique Christians (in Ireland and elsewhere) could speak about politics. Much late antique scholarship on the "secular" assumes it was a passing phase ending in Christianization, but this research argues that "secularity" retained its importance in societies where Christians constantly debated and disagreed over where the boundaries of the "Christian" lay.